(untitled) (Conferencea, 2024)
Morphological changes in the gastric mucosa in critically ill patients on artificial lung ventilation (ALV) are a serious problem in intensive care and are associated with a high risk of complications from the gastrointestinal tract. In critical conditions and prolonged ALV, destructive processes occur, such as edema, hyperemia, erosions and ulcers of the gastric mucosa, which is caused by impaired microcirculation, stress, hypovolemia and the effects of drugs. These changes significantly increase the risk of gastrointestinal bleeding and other complications, which can worsen the prognosis and increase mortality among patients. This article discusses the key mechanisms of gastric mucosal damage development in patients on mechanical ventilation, including barrier function impairment, tissue ischemia, inflammatory reactions, and the impact of drug therapy. Modern approaches to the prevention and treatment of these conditions are described, including the use of antisecretory drugs, normalization of water-electrolyte balance, and provision of adequate tissue perfusion. Understanding these processes and timely intervention can reduce the incidence of complications and improve treatment outcomes in critically ill patients.